Getting Started in Butterfly Gardening - Richard K. Sprenkel (EDIS)
This publication was developed for individuals who are just getting started in butterfly gardening or who want to pursue the hobby with a good chance of success. This document is ENY-722, one of a series of Entomology and Nematology Department, Florida Cooperative Extension Services, Institute of Food and Agricultural Sciences, University of Florida. Publication Date: February 2005.